2010
DOI: 10.1259/bjr/27446907
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hypertrophic olivary degeneration following surgical resection of a posterior fossa epidermoid cyst

Abstract: Hypertrophic olivary degeneration is a result of a primary lesion damaging the dento-rubro-olivary pathway. It is a transynaptic form of degeneration and is unique, causing hypertrophy rather than atrophy of the inferior olivary nucleus. We report a case of bilateral hypertrophic olivary degeneration following surgical excision of a posterior fossa epidermoid cyst and review the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Contralateral HOD is thought to occur when the lesion disrupts the superior cerebellar peduncle or dentate nucleus. Bilateral HOD is thought to occur when lesions involve both the red nucleus or the central tegmental tract (CTT) and the dentate nucleus or the superior cerebellar peduncle …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral HOD is thought to occur when the lesion disrupts the superior cerebellar peduncle or dentate nucleus. Bilateral HOD is thought to occur when lesions involve both the red nucleus or the central tegmental tract (CTT) and the dentate nucleus or the superior cerebellar peduncle …”
Section: Discussionmentioning
confidence: 99%
“…A lesion occurring in this dentato‐rubro‐olivary pathway (DROP) can result in HOD (Fig ) . A variety of causative lesions have been described including infarction, toxic, trauma or surgery, tumor, vascular malformations or hemorrhage . Unilateral cases have been reported to significantly outnumber bilateral cases, perhaps due to the fact that previously reported cases of HOD in the literature have focused on identifying HOD secondary to a structural lesion in the DROP .…”
Section: Background and Purposementioning
confidence: 99%
“…We postulate that the HOD was caused by surgical disruption of the central tegmental tract that connects the red nucleus and the inferior olive. Other investigators have also reported development of HOD after surgery [7,8]. RT may have played a contributory role, as HOD has been described after targeted radiosurgery [9], although a pure radiation effect is thought unlikely, as are direct effects on the triangle from the tumor itself or from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, the incidence of these symptoms varies. 2,5,8 Some reports describe HOD occurring after surgical resection of a brain tumor, [5][6][7] but HOD is rarely caused simply by a tumor in the GuillainMollaret triangle. 8,9 We believe this case report represents theˆrst published description of HOD following GKRS for a brain tumor.…”
Section: Discussionmentioning
confidence: 99%